Osteochondritis dissecans of the knee associated with mechanical overload - Weiden, Goran van der; van Cruchten, Stijn; van Egmond, Nienke; Mastbergen, Simon C.; Husen, Martin; Saris, Daniël B.F.; Custers, Roel J.H. (The American journal of sports medicine, 2024)
Background: Osteochondritis dissecans (OCD) of the knee is a rare but potentially incapacitating disorder in which subchondral bone detaches, leading to an osteochondral fragment that can become unstable and progress into a loose body. The exact cause is unknown, although several biological and mechanical factors have been described. - Purpose: To provide insight into epidemiological data of a large cohort of patients affected by OCD of the knee and to identify potential factors contributing to the cause of this disorder. - Study Design: Cross-sectional study; Level of evidence, 3. - Methods: A total of 236 patients (259 knees) affected by OCD were included in our Knee Registry (2005-2022) and retrospectively analyzed. Patient characteristics were extracted from the medical records. Location and International Cartilage Regeneration & Joint Preservation Society grade (1-4) of OCD were assessed using magnetic resonance imaging. If available, a full-leg standing radiograph was used to assess alignment. Additionally, a statistical scoring system for instability risk was created. - Results: A total of 263 OCD lesions were identified in 259 knees, 66.2% on the medial femoral condyle (MFC), 26.6% on the lateral femoral condyle (LFC), 3.8% on the trochlea, 2.7% on the patella, and 0.8% on the lateral tibia plateau. Male patients made up 57.6% of the sample, which had a mean age of 21.8 years. A very high percentage of patients (77.1%; n = 182) practiced sports, of whom 67.6% (n = 123) were engaged in high-impact sports. The location of the OCD lesions and the leg alignment (n = 110) were significantly correlated: MFC lesions were associated with more varus than valgus alignment (47.5% vs 11.3%) and patients with LFC lesions had more valgus than varus alignment (46.7% vs 20.0%; P = .002). Based on age, smoking, sports activity, and preceding trauma, a multivariable scoring system (0-11 points) was created. An increased risk of lesion instability was associated with an increased score: 29.0% at 0 points and 97.0% at 11 points. - Conclusion: This study provides detailed epidemiological data for 236 patients affected by OCD of the knee. Older age, smoking, inactivity, and preceding trauma were predictive for instability of OCD lesions. There was an association between OCD of the MFC and varus malalignment and between OCD of the LFC and valgus malalignment. This finding, in combination with the high percentage of patients practicing high-impact sports, suggests an important role for mechanical overload in the pathogenesis of OCD.
Zuerst online veröffentlicht: 2. Januar 2024
Gesehen am 27.03.2024